SOX9/miR-203a axis drives PI3K/AKT signaling to promote esophageal cancer progression. (1st January 2020) - Wang, Lianghai; Zhang, Zhiyu; Yu, Xiaodan; Li, Qihang; Wang, Qian; Chang, Aimin; Huang, Xiaoxi; Han, Xueping; Song, Yangguang; Hu, Jianming; Pang, Lijuan; Hou, Jun; et al.
Abstract: Deregulation of SOX9 in esophageal cancer has been reported. However, the regulatory mechanisms underlying SOX9 during esophageal squamous cell carcinoma (ESCC) progression remain poorly understood. Here, we independently confirmed the increased SOX9 expression in two ESCC cohorts and its correlation with poor prognosis. We demonstrated that SOX9 was required for maintaining self-renewal, motility, and chemoresistance in vitro and that ectopic expression of SOX9 promoted tumorigenicity in vivo. Screening for potential SOX9-regulated miRNAs revealed that target genes of differentially expressed miRNAs were enriched in the PI3K/AKT signaling pathway and identified the downregulated miR-203a as a candidate. Mechanistically, SOX9 activation caused repression of miR-203a transcription by binding to miR-203a promoter, thus preventing the miR-203a-mediated inhibition of multiple PI3K/AKT/mTOR components, including PIK3CA, AKT2, and RPS6KB1 . The association between SOX9 expression and PI3K/AKT/mTOR signaling was further validated in clinical samples. Moreover, rapamycin treatment attenuated the SOX9-mediated malignant phenotypes and potentiated cisplatin-mediated inhibition of tumor growth. Together, these findings uncover a novel activation of the PI3K/AKT pathway by the SOX9/miR-203a axis and define a subgroup of patients who may benefit from targeted therapy. Highlights: Elevated SOX9 expression is independently confirmed in two ESCC cohorts. Target genes of differentially expressed miRNAs regulated by SOX9 are enriched in the PI3K/AKT signaling. SOX9 suppresses miR-203a transcription, thus preventing the miR-203a-mediated inhibition of the PI3K/AKT/mTOR pathway. Rapamycin attenuates the SOX9-mediated malignant phenotypes and potentiates the inhibition of tumor growth by cisplatin. Using the SOX9 level as a patient stratification biomarker might form the basis of a promising treatment for ESCC.